Al-khilafah al-Islamiyyah: Nazrah Muqaranah bayna Hizbu al-Tahrir al-Falistini wa al-Sunnah al-Nabawiyyah - Sahabuddin S.; Waskito Wibowo; Sholeh Taufiq (Islamika Inside: Jurnal Keislaman dan Humaniora, 2020)
Abstract: This research aims to clarify the reality of the Islamic Caliphate in light of the Sunnah of the Prophet. It also aims to know the truth of Hizbut-Tahrir, its opinions and efforts in establishing the Islamic Caliphate, so that the aspects of agreement and disagreement become clear. In writing this research, the researcher follows the analytical method, in that it relies on library sources and references instead of data taken from the applied study in society. Among the most important findings of the researcher is: The consensus of the majority of scholars - including Al-Nawawi - and Hizbut-Tahrir that the Islamic Caliphate is its goal is to manage religious affairs and organize worldly matters, and their disagreement over the appointment of the caliph and the conditions for its convening.